Perspektif Teori Trait and Factor serta Penerapannya dalam Bimbingan dan Konseling Karir - Fitriani Syamal; Afdal Afdal; A Muri Yusuf (SCHOULID: Indonesian Journal of School Counseling, 2021)
One of the things that often happens to individuals after graduating from education is that many do not know what work to do, where to work, and do not understand how to have a career according to their interest and talents. Trait and factor is one of the theories in career guidance and counseling that helps individuals to improve their understanding ability to have a career. Career guidance and counseling services using trait and factor theory can assist individuals in finding and determining their careers. Career guidance and counseling is one of the services provided to individuals/students to help gain an undestanding of careers.  Career guidance and counseling using trait and factor theory is proven to be able to improve and develop individual/students career abilities in a better direction. Counselors are people who play an important role in providing career guidance and counseling services. This is also intented so that individuals are able to develop their talents, interest and abilities in a career.